Role of cyclic adenosine 3',5'-monophosphate on cessation of respiration in ultraviolet-irradiated Escherichia coli. - Swenson, P A (1977)
The addition of cyclic adenosine 3',5'-monophosphate (cAMP) to ultraviolet-irradiated Escherichia coli B/r cultures causes additional cells to cease respiring and to die. These effects of cAMP are greater on glucose-grown cells, where the effects of ultraviolet radiations alone are smaller and where the intracellular concentrations of cAMP are known to be lower.